We the people of India: a story of gangland democracy - "Dhar, Maloy Krishna" (New Delhi, 2008)
This is the story of the nation that boasts of being the largest democracy. The novel undertake tortuous journeys through the political minefield and discovers that moneybags, muscle power and criminal fringes have hijacked Indian democracy. Satya Sarthi is a psephologists and wants to bring about a change in the system.
Keywords: Novel